Bypassing a separated instrument in mandibular first premolar with two canals – a case report / Mohd Nazrin Isa and Aws Hashim Ali AL-Kadhim - Isa, Mohd Nazrin; AL-Kadhim, Aws Hashim Ali (Faculty of Medicine, 2021)
Fracture of an endodontic instrument will impair the debridement procedure and thus affects the endodontic outcome. This case report focuses on the management of separated instrument and highlights the anatomical variation of mandibular first premolar. An in-depth knowledge on the internal anatomy of this particular tooth as well as following a proven and safe technique as a guideline is important in preventing these endodontic mishaps.